Angioplasty and stenting for the proximal anastomotic stenosis of a brachio-axillary bypass graft using a helical interwoven nitinol stent: A case report. Issue 50 (December 2017) - Cho, Soo Buem; Choi, Ho Cheol; Bae, EunJin; Park, Tae Jin; Baek, Hye Jin; Park, Sung Eun; Ryu, Kyeong Hwa; Moon, Jin Il; Choi, Bo Hwa; Bae, Kyungsoo; Jeon, Kyung Nyeo
Abstract: Rationale: Thrombosis due to anastomotic site stenosis is the most common complication in patients with brachio-axillary arteriovenous graft (AVG). Intravascular stent placement may play a special role in the salvage of dialysis grafts that have been previously performed percutaneous angioplasty or surgical procedure on the graft. Herein, we applied a novel stent named Supera which has a high degree of flexibility and resistance to external compression for treating a patient with recurrent venous anastomotic stenosis of brachio-axillary AVG. Patients concerns and diagnoses: We report a case of the patient with end-stage renal disease who presented with brachio-axillary AVG malfunction. Interventions: The patient underwent repeated percutaneous angioplasty with thrombectomy for total graft occlusion, and we placed the Supera stent to salvage the graft. Outcomes: Postprocedural Doppler ultrasonography did not show any restenosis on the 1- and 3-month follow-up periods, and average flow volume in the stent was >1000 mL/min. And he has been on dialysis for 6 months without any problems after stent placement. Lessons: The Supera stent is a useful treatment option of interventional procedure for recurrent venous anastomotic stenosis of brachio-axillary AVG in the clinical practice.